Restorasi Indonesia sebagai Visi dan Strategi Komunikasi Politik Surya Paloh di Era Digital - M. Taufiq Hidayah Tanjung; Iskandar Zulkarnain; Mailin Mailin (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2026)
This study examines Restorasi Indonesia as a political vision articulated through the political communication strategy of Surya Paloh in the digital era, in response to the increasing mediatization of political discourse within Indonesia’s contemporary democratic landscape. The research addresses how the vision of national restoration is constructed, disseminated, and transformed through digital political communication practices to influence public perception and political engagement. Employing a qualitative approach, this study utilizes discourse analysis to investigate Surya Paloh’s communication strategies across digital platforms, including speeches, social media narratives, and mediated political messaging. The findings indicate that the articulation of Restorasi Indonesia operates not merely as an ideological construct but as a communicative framework that adapts to the dynamics of digital media through symbolic narratives, strategic framing, and audience-oriented messaging. This transformation reflects a shift from conventional political mobilization toward digitally mediated persuasion, enabling the political vision to maintain relevance in a rapidly evolving information ecosystem. The study argues that the effectiveness of Restorasi Indonesia as a political vision is closely linked to its communicative adaptability, where strategic digital engagement becomes central to shaping political legitimacy and sustaining ideological resonance in the public sphere.